Posted by **tracy** on Wednesday, October 19, 2011 at 1:38pm.

When factored completely, 4x^2y - 8x^2y^2 + 6xy^2 = 2xy(2x - 4xy + 3y).

true or false

- algebra -
**Luke**, Wednesday, October 19, 2011 at 1:45pm
True

## Answer this Question

## Related Questions

algebra - When factored completely 4x^2y-8x^2y^2=2xy(2x-4xy+3y)

algebra - When factored completely 4x^2y-8x^2y^2=2xy(2x-4xy+3y)

7th grade health true or false - 11. Disagreements are a normal part of life. (1...

Physical Ed - 11. Disagreements are a normal part of life. (1 point) True False ...

Algebra - Simplify each of the following expressions into simplest terms. a) {[-...

algebra 1 - the difference between 2x2+4xy-3 and x2-2xy-4 is I will be happy to ...

Algebra - What is the factored form of the following expression? x2 – 4xy – 21y2...

math - Please check. (4xy^2)(3x^-4y^5) = 12x^-3y^7 (2x)^5 (3x)^2 = 288x^7 (-3x^2...

Math - Can 2xy - y - 1 be factored out? How? about all you can do is take the ...

math - (4xy^2)(3x^-4y^5) = 12x^-3y^7 (2x)^5 (3x)^2 = 288x^7 (-3x^2)^4 = 81x^8 ...